2022
DOI: 10.3390/jcm11164741
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Laryngeal Cancer Surgery after Open Partial Horizontal Laryngectomies with Lateral Cervical Approach

Abstract: Background: Open partial horizontal laryngectomies (OPHL) are one of the surgical techniques used for the conservative management of laryngeal cancers. The aims of this study are to analyze the oncological and functional results of a group of patients affected by laryngeal squamous cell carcinoma (LSCC) treated with OPHL, performed using a minimally invasive technique. Methods: This is a prospective case–control study. We enrolled 17 consecutive patients with LSCC treated with OPHL through a lateral cervical a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Voice Handicap Index Information about perceived voice quality was assessed by standardized scales as the Voice Handicap Index 10 (VHI-10) in one study [4], and VHI is a 30item scale used in one different study [3]. The VHI is a 30-item instrument designed to examine the selfperceived emotional, physical, and functional effects of patients' voice dysfunction [10,11]. Gugatschka et al [3] reported in 34 patients no statistically significant difference in terms of mean VHI-30 German Version total score (p = 0.6), that was 8.1 (±9.5) in PCOS patients and 10.1 (±11.5) in the control group, respectively, or in subscales.…”
Section: Patient-reported Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…Voice Handicap Index Information about perceived voice quality was assessed by standardized scales as the Voice Handicap Index 10 (VHI-10) in one study [4], and VHI is a 30item scale used in one different study [3]. The VHI is a 30-item instrument designed to examine the selfperceived emotional, physical, and functional effects of patients' voice dysfunction [10,11]. Gugatschka et al [3] reported in 34 patients no statistically significant difference in terms of mean VHI-30 German Version total score (p = 0.6), that was 8.1 (±9.5) in PCOS patients and 10.1 (±11.5) in the control group, respectively, or in subscales.…”
Section: Patient-reported Outcomesmentioning
confidence: 99%
“…However, this study does not report the incidence of patients with a pathological score (cutoff >11). The VHI-10 is a valid instrument, with a slight loss of information with respect to the VHI-30, to quantify the patients' own perception of voice [10,11]. According to Aydin et al [4], pathologic scores in VHI-10 were found in a total of 52 women, in 6.7% (2/30) of patients affected by PCOS compared with 0% (0/22) of controls.…”
Section: Patient-reported Outcomesmentioning
confidence: 99%